Oxford new syllabus primary Mathematics workbook 1B for grade 1 - Yee, Dr Foong Pui (Karachi : Oxford university press, 2019)
The "Oxford New Syllabus Primary Mathematics Workbook 1B" is a supplementary workbook designed to reinforce and expand upon the concepts introduced in the primary mathematics curriculum for Grade 1. It focuses on helping students practice and apply mathematical skills through a variety of exercises and activities.
Keywords: Mathematics : Workbook